Patients who experience systemic lupus erythematosus and leg ulcer: phenomenological approach - Eline Lima Borges; Selisvane Ribeiro da Fonseca Domingos; Larissa Pereira de Carvalho Campos; Josimare Aparecida Otoni Spira (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To understand the experience of a woman with systemic lupus erythematosus and leg ulcers with cutaneous calcinosis. Methods: An experience report based on the social phenomenology of Alfred Schutz, conducted with a young woman undergoing treatment in an outpatient service. Results: The disease manifested itself in adolescence and brought emotional instability associated with body image concern and social isolation. The discontinuation of the studies triggered financial limitations with implications for treatment. The presence of ulcers aggravated by skin calcification makes the process of getting sick tiring and painful. Interpersonal relationships are resources for coping with situations experienced. Final considerations: Patients with lupus may have social, affective, and family life, even in the face of the limitations imposed by the disease. However, the emergence of leg ulcer with calcinosis changes this situation.